The effect of corporate governance and risk taking on financial performance of Malaysian banks - Fazel Mohammadi Nodeh, 1985-, author; Melati Ahmad Anuar, supervisor; Suresh Ramakrishnan, supervisor; Fakulti Pengurusan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Pengurusan)) - Universiti Teknologi Malaysia, 2016